2021
DOI: 10.3389/fmicb.2021.663924
|View full text |Cite
|
Sign up to set email alerts
|

Coculture, An Efficient Biotechnology for Mining the Biosynthesis Potential of Macrofungi via Interspecies Interactions

Abstract: Macrofungi, which are also known as mushrooms, can produce various bioactive constituents and have become promising resources as lead drugs and foods rich in nutritional value. However, the production of these bioactive constituents under standard laboratory conditions is inefficiency due to the silent expression of their relevant genes. Coculture, as an important activation strategy that simulates the natural living conditions of macrofungi, can activate silent genes or clusters through interspecific interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 56 publications
0
17
0
1
Order By: Relevance
“…In the specific interaction between A. nidulans and Streptomyces rapamycinicus , activation of the silent orsellinic acid gene cluster was mediated by manipulating the chromatin-based epigenetic factor gcnE in the eukaryotic partner by bacterial signal transduction ( 15 , 16 , 18 ). Cryptic SM stimulations were also observed in fungal-fungal cocultivation of P. citrinum with B. felina , Trichoderma hamatum with Chaunopycnis sp., Trametes robiniophila with Pleurotus ostreatus , and Aspergillus fischeri with Xylaria cubensis ( 13 , 14 , 55 , 56 ). Despite increasing research on fungal-fungal interactions for activation of silent BGCs, the complex regulation involved in fungal metabolism triggered by cocultivation still remains uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…In the specific interaction between A. nidulans and Streptomyces rapamycinicus , activation of the silent orsellinic acid gene cluster was mediated by manipulating the chromatin-based epigenetic factor gcnE in the eukaryotic partner by bacterial signal transduction ( 15 , 16 , 18 ). Cryptic SM stimulations were also observed in fungal-fungal cocultivation of P. citrinum with B. felina , Trichoderma hamatum with Chaunopycnis sp., Trametes robiniophila with Pleurotus ostreatus , and Aspergillus fischeri with Xylaria cubensis ( 13 , 14 , 55 , 56 ). Despite increasing research on fungal-fungal interactions for activation of silent BGCs, the complex regulation involved in fungal metabolism triggered by cocultivation still remains uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, coculturing was broadly used in exploring unexplored biosynthetic potentials, such as new enzymes and metabolites, that may be employed in various fields in the future, including agriculture, medicine, and industry 28 . For example, enhancing FA composition in the soybean fermentation process through coculturing with B. subtilis and R. oligosporus 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the coculture strategy, which simulates the symbiotic relationship of organisms in nature, can easily activate silenced gene clusters through the interaction between strains. [2,5] In our previous work, we have found that Pleurotus ostreatus SY10 can produce unusual anti-fungal sesterterpenes, postredienes A -C, when cocultured with Trametes robiniophila Murr. SY636.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many methods have been used to explore the metabolic potential of edible fungi, such as metabolic engineering and epigenetic modification, while it is still difficult to efficiently manipulate gene expression in most edible fungi. In contrast, the coculture strategy, which simulates the symbiotic relationship of organisms in nature, can easily activate silenced gene clusters through the interaction between strains [2,5] …”
Section: Introductionmentioning
confidence: 99%